2013
DOI: 10.1089/cyber.2012.0513
|View full text |Cite
|
Sign up to set email alerts
|

Self–Other's Perspective Taking: The Use of Therapeutic Robot Companions as Social Agents for Reducing Pain and Anxiety in Pediatric Patients

Abstract: The study examined whether complementary therapy using robotic companions as social agents reduced pain and emotional anxiety in pediatric patients. A total of 18 patients, aged 6-16, and 18 parents participated in the study. The study explored whether the use of robotic animals as companion animals could reduce pain and emotional anxiety in patients and their parents. The study identified when robot-assisted therapy was most effective (alone or together with parent). The study hypothesized that engaging in ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 34 publications
0
66
0
Order By: Relevance
“…One study showed significant reductions in anxiety, anger and depression in patients with cancer in a social robot-assisted therapy group compared with a psychotherapy (control) group 24 25. In other work, hospitalised children who interacted with a robot together with their parent demonstrated greater decreases in pain and anxiety compared with those who interacted with the robot alone 26. Children with cerebral palsy had a significantly higher interaction level with an exercise demonstration robot (although worse motor performance) than typically developing children, demonstrating the feasibility of the robot for use as a motivating and engaging therapeutic tool 27.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed significant reductions in anxiety, anger and depression in patients with cancer in a social robot-assisted therapy group compared with a psychotherapy (control) group 24 25. In other work, hospitalised children who interacted with a robot together with their parent demonstrated greater decreases in pain and anxiety compared with those who interacted with the robot alone 26. Children with cerebral palsy had a significantly higher interaction level with an exercise demonstration robot (although worse motor performance) than typically developing children, demonstrating the feasibility of the robot for use as a motivating and engaging therapeutic tool 27.…”
Section: Resultsmentioning
confidence: 99%
“…Another previous study specifically addressed medical-related fears and anxiety using Paro, a soft robotic seal robot. Paro acted similar to that of a companion animal and did not speak to the patient or offer any medical information [8]. e design of our study allows a more seamless integration of IVEY as a helper to the child life specialist who facilitates child coping and provides medical information.…”
Section: Discussionmentioning
confidence: 99%
“…ey establish communication and create a shared relationship without touching the child by utilizing embodiment, personality, empathy, and adaptation skills. ese robots have been shown to reduce pain and anxiety associated with hospitalization [8,9] and during short procedures such as vaccine administration [10] in a limited number of studies that generally use the robot solely as distraction. Preliminary work from the University of Southern California Interaction Lab has shown that SARs that display empathy create an interaction perceived as more positive by the adults [11].…”
Section: Introductionmentioning
confidence: 99%
“…A first study conducted by Okita (2013) with 18 children with cancer (6–16 years) and their parents used the animal robot Paro. Paro is a seal-like robot with the ability to interact in a multimodal way: it talks, moves, and reacts to touch.…”
Section: Robots and Childrenmentioning
confidence: 99%